Structural basis for mechanotransduction in a potassium-dependent mechanosensitive ion channel - Jonathan Mount; Grigory Maksaev; Brock T. Summers; James A. J. Fitzpatrick; Peng Yuan (Nature Communications, 2022)
Mechanosensitive ion channels mediate biological force sensation, but the underlying mechanism remains poorly understood. Here, authors present the structural basis of mechanotransduction in an ion channel revealed by cryo-electron microscopy.